Increase in Abstention Rates in the 2024 Election: Decreasing Community Participation in Using the Right to Vote: Ghaitsa Zahira Shofa, Ristania Tri Widiarti2*, Rochmawati Ing Lestari, Nur Hasanah - Ghaitsa Zahira Shofa; Ristania Tri Widiarti; Rochmawati Ing Lestari; Nurhasanah (Samudra Publisher, 2024)
This article discusses the challenges and efforts in overcoming the phenomenon of abstention in general elections with a holistic approach. Abstention, as an indicator of declining political participation, is a serious concern in maintaining the health of democracy. Through an analysis of the factors that cause abstention from social, political, economic, and psychological aspects, this article identifies the importance of improving political education, accessibility of political processes, transparency, and inclusiveness of political culture. Proposed efforts include socialization campaigns, political system reform, strengthening political parties, and utilizing information technology. It is hoped that with an integrated approach, people can engage more actively in the democratic process, minimize abstention, and strengthen representation and fairness in elections.